First Best-Ansatz. CO2-Handel in der Autoindustrie. - Dudenhöffer, Ferdinand (Deutscher Verkehrs-Verl., 2007)
Obgleich eine Fülle technologischer Ansätze vorhanden ist, verfehlt die europäische Automobilindustrie die selbstgesteckten Ziele zur Verringerung der CO2-Emissionen. Ein wichtiger Grund hierfür ist die geringe Zahlungsbereitschaft der Autokäufer für treibstoffsparende Technologien. Mit einem einfachen Handelssystem für Kohlendioxidemissionen sind die von der EU-Kommission vorgegebenen Ziele von durchschnittlich 130 Gramm CO2 pro Kilometer schnell, unkompliziert und nachhaltig zu erreichen. difu

Car manufacturers will not be able to meet their self-imposed target of the lower average CO2 level of 140 grams/km for new cars sold in Europe in 2008. The EU has reacted by limiting the CO2 standard level for new cars sold to 130 grams/km by 2012 but the open question is how to achieve this target. The most simple and effective approach for the car manufacturing industry would be to negotiate CO2 levels. The report presents a CO2 negotiating model for the manufacturing industry to show that the car sales market could adequately cope with variable price levels - related to CO2 levels - for new cars. The advantages would be the immediate application of the proposed standards, compatibility with other business sectors concerning CO2 levels, and no withdrawal of funds from the motor car market. Negotiating CO2 levels would appear to be the best solution for the car manufacturing industry. difu
Keywords: Umweltschutz; Verkehr; Emission; Kraftfahrzeug; Industrie; Kohlendioxidminderung; Automobilindustrie; Treibstoffverbrauch; Emissionshandel; Produktinnovation; Kraftfahrzeugtechnik